Simplified resonant parameter design of the asymmetrical CLLC-type DC transformer in the renewable energy system via semi-artificial intelligent optimal scheme - Huang, Jingjing (2022)
Asymmetrical CLLC-type dc transformers (ACLLC-type DCTs) are becoming more and more popular in the renewable energy system, thanks to the bidirectional power transmission (PT), high power density, and low-cost sensorless open-loop control. Nevertheless, the resonant frequency is not constant due to variations of the operation power and temperature in practice, which may make DCT lose its required voltage conversion gain and deteriorate the PT ability. This poses a challenge on the design of circuit parameters, especially when the open-loop scheme is usually recommended for the ACLLC-type DCT in the renewable energy system. Therefore, a semi-artificial intelligence (semi-AI)-based simplified parameter design approach is put forward in this paper for ACLLC-type DCT. It replaces all unknown parameters with two intermediate parameters through certain manipulations, and then utilizes a very simple computer-assisted procedure to optimally design the parameters of the ACLLC-type DCT. In addition, a detailed design example with a special planar transformer is presented via the aid of ANSYS Maxwell to achieve the desired resonant parameters of the ACLLC-type DCT. Finally, the proposed semi-AI-based method is experimentally demonstrated in a real renewable energy system prototype.